Purchasing intention, family values and social media usage affecting online purchasing habits among youths - Hussain, Souhaila; Illiasu, Adam; Wok, Saodah (2018)
Malaysian statistics show a trend of continued growth in the e-commerce industry; this research stresses on the importance of catering to the needs and inclinations of youths regarding online purchasing intentions and habits. The objective of this research is to study the effects of family values and social media usage for commercial purposes on the purchasing intention and subsequently the purchasing habits of post-graduate university students. This research contributes to the existing body of knowledge on consumer online purchasing behaviour through the underlying framework of the Theory of Planned Behaviour. A quantitative research design using the survey method was followed, employing a questionnaire to gather data from students. Data were analysed through the statistical analyses. The results indicate that the purchasing intention partially mediates the relationship between family values and social networking sites’ commercial usage towards the purchasing habit. The purchasing intention also partially mediates the relationship between the social networking sites commercial usage and the purchasing habit. The paper concludes by stressing the importance of catering to the needs and inclinations of consumers while understanding their cultural values. The study provides managerial implications to marketing managers targeting audiences through online platforms.